Impact of daily vitamin D3 supplementation on the risk of vitamin D deficiency with the interaction of rs2282679 in vitamin D binding protein gene (GC) among overweight and obese children and adolescents: A one-year randomized controlled trial - Asghari, Golaleh; Yuzbashian, Emad; Nikparast, Ali; Najd Hassan Bonab, Leila; Mahdavi, Maryam; Daneshpour, Maryam S.; Hosseinpanah, Farhad; Mirmiran, Parvin (Frontiers in Nutrition, 2022)
Background: The rs2282679 polymorphism in the vitamin D binding protein (DBP) gene may influence the response to vitamin D supplementation. Therefore, we examine the effect of one-year vitamin D supplementation on vitamin D deficiency (VDD) with the interaction of rs2282679 polymorphism in overweight and obese children and adolescents. Methods: The participants (n=300) were part of a randomized controlled trial who received a daily supplement of either 1000 IU or 2000 IU or four supplements of 1000 IU weekly (equal to 600 IU daily) of vitamin D3 for 12 months. Genotyping was performed using amplification refractory mutation system polymerase chain reaction (ARMS-PCR). Results: The mean of 25(OH)D values at baseline for participants with the TT, TG, and GG genotypes were 15.4, 14.4, and 10.8 ng/ml, respectively, and were not different between the three genotype groups (P=0.062). A significant reduction in VDD was observed after vitamin D supplementation with dosages of 1000 or 2000 IU compared to 600 IU. No significant association of genotypes with risk of VDD was observed in each intervention group after vitamin D supplementation, except, that individuals with TG genotype showed a higher risk of VDD compared to those with TT genotype in the 2000 IU group after 6 months of supplementation [odds ratio (95 % CI): 6.94; 1.30-37.02]. We observed no interaction between time duration, three genotypes, and dosages with serum 25(OH)D, calcium, phosphorus, alkaline phosphatase, and parathyroid hormone levels. Conclusions: Response to vitamin D supplementation by three doses of 600 IU, 1000 IU, and 2000 IU could not be affected by rs2282679 polymorphism during 12 months in overweight and obese children and adolescents.